العوامل الاقتصادية والاجتماعية لاختيار مهنة الطب من وجهة نظر الطالبات السعوديات: دراسة تطبيقية على جامعة القصيم - Khawaja, Muhammed Junaid (مجلة العلوم الإدارية و الإقتصادية, 2015)
The study is aimed at exploring Saudi female students’ attitudes toward studying medicine. The current study sample consisted of 105 randomly selected female students at Qassim University. The study is based on a questionnaire prepared for this purpose which comprised of 37 questions including the demographic information. Regression analysis reveals that anticipated salary, desire to learn new things, and having a good job are significant explanatory variables. The regression also shows that female students from high income families are more likely to choose medical profession. Factor Analysis Technique is used to identify the factors most important for explaining the motivation for pursuing medical profession. The factor analysis reveals that factors titled as human capital creation, social capital acquisition and social environment are the most important in explaining variation in the motivation for choosing the medical profession.